The effectiveness of psychological support for the development of the indicators of personal functioning of family members with problem children - Mushkevych , Myroslava (Psychological Prospects Journal, 2021)
Goal. The process of psychological support of families with problem children is aimed at studying the characteristics of the personal functioning of adult members of the family system, their psychological state, the range of problems, tasks to solve them, immersion in real family life. Methods. Stages of the psychological research involve the initial diagnosis and discussion of the results of standardized and projective methods; study of gaps in the knowledge of family members about the peculiarities of personal functioning at the level of marital and parental subsystems and the provision of specifically necessary information for the development of psychological culture; counseling on improving personal and interpersonal interaction; elaboration of individual and family dysfunctions by psychotherapeutic methods by means of drawing up a diagram, writing a fairy tale, description of a metaphorical family chest.Results. Content resources of psychological support are focused on prognostic and significant personal predictors of development of personal functioning of adult members of the family system: low level of expression of "hypoprotection"; positive attitude towards the child; low level of expansion of the sphere of parental feelings; cooperation with the child; inversely proportional schizoid type of accentuation; low level of symbiosis with the child; low level of expression "indulgence"; inversely proportional level of minimum sanctions; inversely proportional epileptoid type. Conclusions. The proposed components of psychological support help to overcome the negative psychological symptoms and increase the functionality of the family system. The symptoms and problems identified at the psychodiagnostic stage are considered as the result of suboptimal, dysfunctional interactions of family members, and not as an attribute of one or another of its members. The foci of psychoeducational, psychoconsultative and psychotherapeutic influence were four non-constructive personal and interpersonal factors, such as "introverted-pedantic personal disposition", "dominant-aggressive personal disposition", "psychasthenic personal disposition", " encourage-educational disposition".